Enhancing the performance of bituminous hot mix pavements with graphene nanoplatelet additive using taguchi optimization - Suna Işık; Fatih İrfan Baş (Case Studies in Construction Materials)
Flexible pavement, where bitumen serves as the binding material, is the most widely used type of pavement due to its many advantages. Hot mix asphalt (HMA) pavements are often selected for their ability to create safe, comfortable, cost-effective, and sustainable roadways. However, HMA pavements deteriorate due to traffic, climatic conditions, and environmental influences. To improve their resistance to these challenges, bitumen is modified with various additives. This study utilized graphene nanoplatelet (GNP) to modify bitumen due to its strength, flexibility, and cost-effectiveness. Based on the experimental plan established by the Taguchi method, 16 different mixtures were prepared using four parameters, each with four levels: GNP rates of 0 %, 0.35 %, 0.70 %, and 1 %; mixing temperatures of 145°C, 160°C, 175°C, and 190°C; mixing times of 15, 30, 45, and 60 min; and mixing speeds of 1000, 2000, 3000, and 4000 rpm. A comprehensive set of tests, including penetration, softening point, flash point, elastic recovery, rotational thin film oven test (RTFOT), Fourier transform infrared spectroscopy (FTIR), and Marshall design experiments, were conducted on the mixtures to evaluate the influence of the selected parameters and levels on the properties of bitumen. The bitumen's temperature susceptibility and stiffness modulus were analyzed, providing insights into its behavior under varying temperature conditions. The results of the study indicated that the GNP additive led to a reduction in the RTFOT mass loss and softening point of pure bitumen, while increasing the penetration, flash point, elastic recovery, and Marshall stability. The multiple response performance index (MRPI) optimizations identified the optimal levels as a GNP rate of 0.70 %, a mixing temperature of 145°C, a mixing time of 15 min, and a mixing speed of 2000 rpm. GNP contributed to reduced energy consumption and ecological advantages by lowering the optimal mixing temperature to 145°C. It reduced the plastic deformation at high temperatures and improved low-temperature cracking behavior by decreasing the temperature sensitivity of bitumen.